2014
DOI: 10.1007/s10620-014-3464-0
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer in Young Adults

Abstract: The incidence and mortality rates of colorectal cancer (CRC) have been decreasing in adults over 50 years of age, however, these rates have been increasing in adults under 50. The majority of CRC in young adults is sporadic, and is likely due to behavioral and environmental causes, however the exact etiology still remains unclear. The minority of CRC in this population is due to inherited CRC syndromes. Young adults with CRC are often symptomatic (abdominal pain, rectal bleeding), and diagnosis is often delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 55 publications
3
55
0
1
Order By: Relevance
“…The delay in diagnosis may account for the young group showing significantly more stage IV CRC cases than the old group. Past studies have reported a similar tendency that more young CRC patients had advanced stage TNM [10,[12][13][14][15]20] . This result might reflect that young patients have fewer medical examinations than old patients.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The delay in diagnosis may account for the young group showing significantly more stage IV CRC cases than the old group. Past studies have reported a similar tendency that more young CRC patients had advanced stage TNM [10,[12][13][14][15]20] . This result might reflect that young patients have fewer medical examinations than old patients.…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, 22.9% of the young patients in our study underwent colonoscopy owing to a positive FOB test at a medical checkup and were diagnosed as having CRC despite being asymptomatic. A joint guideline in the United States recommends that CRC screening starts at the age of 50 in average-risk individuals [20] , whereas in Japan, the FOB test starting at the age of 40 has been widely used for CRC screening since 1992 [21] . Although preliminary, our result that one-fourth of young CRC patients under the age of 50 was diagnosed through positive FOB test suggests that CRC screening starting at the age of 40 is appropriate and useful for early detection, particularly because the incidence of CRC in younger patients has been increasing over the past few decades [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not evaluate any other potential survival-related factors other than age, it is reasonable to assume that the major causes of mortality in the ≦40 age group would be cancer and accidents, whereas the older age groups would have a higher percentage of mortality caused by co-morbidities. Young age at the onset of CRC has been shown to be associated with inherited CRC syndromes such as MUTYH-associated polyposis, familial adenomatous polyposis (FAP), hereditary nonpolyposis colorectal cancer (HNPCC or Lynch syndrome) and inflammatory bowel disease, suggesting that age of CRC onset is an important indicator of familial history and/or genetic predisposition (9,38). Approximately 2-5% of all CRCs are associated with Lynch syndrome, which is characterized by excessive synchronous and metachronous CRCs, and presence of tumor-infiltrating lymphocytes, signet ring cells, or a strong mucinous component (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CRC among older adults has remained stable, while the incidence among adults aged 20-40 years old has steadily increased (4). Treatment strategies for young as well as old CRC patients consist of CRC staging followed by segmental colectomy, adjuvant chemotherapy, and routine surveillance colonoscopies every year (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that the mortality rates from colon and rectal cancer have been decreasing in adults over 50 years of age. However, these rates have been increasing in adults under 50 34 .…”
Section: Discussionmentioning
confidence: 99%